Reported bruxism and stress experience - Ahlberg J, Rantala M, Savolainen A, Suvinen T, Nissinen M, Sarna S, Lindholm H, (Blackwell Synergy, 2002)
The aim of the study was to analyze whether perceived bruxism was associated with stress experience, age, gender, work role, and occupational health care use among a nonpatient multiprofessional population. Altogether